The effect of drying on the shelflife amaranthus leaves - ATHUL SURESH JUBNA N. K. C NIGHITHA M. T SAHIRA B. M; Dr. Santhi Mary Mathew (Guide); Er. Madhana Supriya (Co-guide) (Tavanur 2015 Department of Food and Agricultural Process Engineering)
used three drying methods, sun drying, cabinet drying and vacuum drying with different paratreatments such as blanching, steam blanching, citric acid and sulphitation. the quality of the dried amaranthus leaves were was expressed in terms of moisture content, ascorbic acid and fibre content and also cooking quality through sensory evaluation.
The effect of drying on the shelflife amaranthus leaves